INFLUÊNCIA DA ADIÇÃO SÍLICA SOLÚVEL NA RESISTÊNCIA À COMPRESSÃO DE PASTAS GEOPOLIMÉRICAS BASEADAS EM METACAULIM - Foscarini, Luis Felipe; Bonsembiante, Francieli Tiecher (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Even though Portland cement is still the main binding agent used by civil construction, the search for new agglomerates has increased. This increase is mainly due to the need for materials with higher technical properties and, mainly, with a lower environmental impact of production. Among the main alternative bonding agents surveyed are geopolymers. Geopolymers are binding agents based on the activation of an amorphous mineral, rich in aluminosilicate (precursor), with a highly alkaline solution (activator). However, in order for these materials to compete commercially with Portland cement, they must have superior technical characteristics. Therefore, in order to obtain high performance of geopolymer materials, the influence of the presence of soluble silicates on the activation solution in the initial mechanical resistance of geopolymer slates was evaluated. The geopolymers were dosed by activating the metacaulim (precursor) with solutions of sodium hydroxide and water, and with combined solutions of alkali sodium silicate, sodium hydroxide and water. Subsequently, the compression strength test was performed. It was found that, among the geopolymer slurries evaluated, those with a higher amount of soluble silica had higher mechanical strengths. In addition, the samples containing sodium silicate in the mixture showed high workability which may have influenced the different mechanical strengths encountered.